ANALISIS DETERMINAN PENGAMANAN FISIK DALAM MENGURANGI RESIKO PENCURIAN DI TOKO WARALABA - Arum Widyarini (Jurnal Kriminologi Indonesia, 2011)
This research explained the determinants analysis of physical security in reducing the risk of crime in franchise stores. This study used quantitative approach to obtain a comprehensive data. Questionnaires are used to gain accurate and objective analysis. Employees evaluated the store where they worked on the physical security tested indicators. The study found that the sequence determinants of physical security performed by franchise stores “X” are based on the level of its application, namely: (1) Key, (2) Lighting, (3) CCTV, and (4) Alarm. In general, physical security on franchise stores “X” were good because it has situational crime prevention in its shop by implementing targets hardening technique as a form of the reduction chance occurrence of the crime, then the risk of shops to be victim also decreased along the reduced opportunities of crime.